2022
DOI: 10.1111/ijac.14127
|View full text |Cite
|
Sign up to set email alerts
|

Study on preformed and in situ spinel containing alumina castable for steel ladle: Effect of fume silica content

Abstract: In the present study, the effect of fume silica content on preformed and in situ spinel containing alumina spinel castable was studied by varying fume silica content at 1 and 4 wt.%. Spinel content for preformed alumina spinel castables varied from 10 to 30 wt.% and MgO content for in situ alumina spinel castables varied from 2.8 to 8.4 wt.%, respectively, and the distribution coefficient (q value) was maintained at .21 and .29 as per Dinger and Funk model. Different castable compositions were processed as per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…96 XRD plots of preformed spinel castable (10-and 20-wt.% spinel) and in situ spinel castable (2.8-and 5.6-wt.% MgO) fired at 1550 • C are shown in Figures 6 and 7, respectively, confirming the previous context. 96 The presence of free periclase (minor) phase in the in situ spinel containing composition is the major difference between the phase content of the in situ and preformed spinel containing castables. The presence of CA 6 improves thermal shock, creep resistance, and the hot strength properties of the castables as a result of toughening mechanisms like crack deflection and crack bridging.…”
Section: Properties Of Alumina-spinel Castablessupporting
confidence: 83%
See 4 more Smart Citations
“…96 XRD plots of preformed spinel castable (10-and 20-wt.% spinel) and in situ spinel castable (2.8-and 5.6-wt.% MgO) fired at 1550 • C are shown in Figures 6 and 7, respectively, confirming the previous context. 96 The presence of free periclase (minor) phase in the in situ spinel containing composition is the major difference between the phase content of the in situ and preformed spinel containing castables. The presence of CA 6 improves thermal shock, creep resistance, and the hot strength properties of the castables as a result of toughening mechanisms like crack deflection and crack bridging.…”
Section: Properties Of Alumina-spinel Castablessupporting
confidence: 83%
“…68 Phase analysis study also confirmed the formation of the hibonite (CA 6 ) phase for 1-wt.% fume silica addition in preformed and in situ spinelbased castables. 96 XRD plots of preformed spinel castable (10-and 20-wt.% spinel) and in situ spinel castable (2.8-and 5.6-wt.% MgO) fired at 1550 • C are shown in Figures 6 and 7, respectively, confirming the previous context. 96 The presence of free periclase (minor) phase in the in situ spinel containing composition is the major difference between the phase content of the in situ and preformed spinel containing castables.…”
Section: Properties Of Alumina-spinel Castablessupporting
confidence: 83%
See 3 more Smart Citations